THE EFFECT OF FINANCIAL LITERACY ON FINANCIAL MANAGEMENT WITH SELF EFFICACY AS A MEDIATION - Dinar Fahza Arvita; Mardiana Mardiana (Universitas KH. Abdul Chalim Mojokerto, 2026)
Students from lower-middle-class economic backgrounds must have greater skills in managing limited finances. This is similar to students receiving scholarships who must manage their own finances. The purpose of this study is to determine the effect of financial literacy on financial management, with self-efficacy as a mediator. This research approach is quantitative descriptive, with the research subjects being students of the Faculty of Economics, UIN Maulana Malik Ibrahim Malang, period 2022. The sample size was 236 respondents, and the population was 576 students. The sampling technique used was simple non-random sampling. The research analysis technique used was SEMPLS. The results of this study indicate that financial literacy has a positive and significant effect on financial management, financial literacy has a positive and significant effect on self-efficacy, self-efficacy has a positive and significant effect on financial management, and financial literacy has a positive and significant effect on financial management through self-efficacy as a mediator.